Indicators for measuring tourism intensification in urban areas through their associative network: Case studies from the Spanish Mediterranean coast - Chamizo-Nieto, Francisco José; Nebot-Gómez-de-Salazar, Nuria; Rosa-Jiménez, Carlos; Reyes-Corredera, Sergio Jesús (Varna University of Management, 2022)
Clustering of tourism-related activities leads to tourism gentrification because of urban tourism. This study proposes a methodology for identifying pattern of tourism intensification in cities. The main objectives were to conduct an in-depth measurement of tourism intensification and to consider the conflict of interest between stakeholders involved. The proposed indicator system is based on several variables measured by neighbourhoods as territorial units: citizen initiatives, population and tourist accommodations and facilities. All indicators were tested in two Spanish port cities: Malaga and Valencia. Geographic Information System mapping showed common patterns in both cities, such as tertiary use concentrated in the old town, new tourist offers around it, and emerging clusters far away. Statistical analysis showed a high spatial correlation between neighbourhoods with several citizen initiatives and a wide range of Airbnb listings or cultural facilities. The spatial analysis and correlations between tourism intensification indicators may serve as a basis for local administrations to propose an urban policy that deals with overtourism in the short and medium terms. This work serves as a basis for new research on urban tourism: redefinition and addition of variables, as well as further development of comparative case studies or field studies that check the datasets.
Keywords: Turismo; Tourism intensification; Touristification; Gentrification; Urban tourism; Overtourism; Indicator system